Reassessing the economic value of advanced level mathematics - Adkins, Michael; Noyes, Andrew (Wiley, 2016)
In the late 1990s, the economic return to Advanced level (A-level) mathematics was examined. The analysis was based upon a series of log-linear models of earnings in the 1958 National Child Development Survey (NCDS) and the National Survey of 1980 Graduates and Diplomates. The core finding was that A-level mathematics had a unique earnings premium of 7-10% at age 33. In recent years, this finding has contributed to the government’s agenda of increasing participation in post-16 study of advanced mathematics in England. Given that the 1958 NCDS participants are now 57 years old, this paper repeats this important work using the 1970 British Cohort Study (BCS). Updated models are used to investigate whether the A-level mathematics premium also existed at age 34 for the 1970 BCS participants. There does appear to be a return of approximately 11% when replicating the original model closely but the robustness of this result depends on the model specification, sample size and the handling of missing data. We consider theoretical explanations of these findings and their implications for policy and future research.